Equity fund ownership and the cross-regional diversification of household risk - Becker, Sascha O.; Hoffmann, Mathias (Journal of Banking & Finance, 2010)
We explore the link between portfolio home bias and consumption risk sharing among Italian regions using household-level information on consumption, income and portfolio holdings. Since equity funds are typically diversified at the national or international level, we use data on equity fund ownership to proxy for regional home bias. Cross-regional patterns of equity fund ownership are qualitatively consistent with simple portfolio theory: regions with more asymmetric business cycles are more diversified because they have higher fund participation rates (the extensive margin of diversification) and higher average holdings of equity funds (diversification’s intensive margin). Also, fund holdings increase with the exposure of non-tradable income components (such as labor or entrepreneurial income) to regional shocks. Finally, interregional consumption risk sharing increases with fund holdings and this effect seems strongest when participation is widespread. Increased equity market participation could substantially improve interregional risk sharing.